2012
DOI: 10.1007/s11300-012-0231-9
|View full text |Cite
|
Sign up to set email alerts
|

SEZ Proliferation in India: Are the Objectives Being Realized?

Abstract: This paper analyzes if the industrial policy framework of the Indian Government with regard to the proliferation of SEZs has satisfied its aims and objectives. The analysis however, shows otherwise. The empirical results show that the policy of the Indian Government has been lopsided, wherein the concentration of SEZs has increased in States which face lower levels of unemployment and a comparably high level of FDI inflow. Further, the concentration of the SEZs has been restricted majorly to the IT industry re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Similar effects occur due to local level regulations and input markets (Greenstone et al 2012 ; Petrin and Sivadasan 2013 ). For India, in particular, Bhatt et al ( 2011 ) have also found strong correlation in establishment of SEZs and areas with higher inflow of foreign investments in India. Therefore, I include the following indicators A dummy for district of the enterprise.…”
Section: Data and Summary Statisticsmentioning
confidence: 94%
“…Similar effects occur due to local level regulations and input markets (Greenstone et al 2012 ; Petrin and Sivadasan 2013 ). For India, in particular, Bhatt et al ( 2011 ) have also found strong correlation in establishment of SEZs and areas with higher inflow of foreign investments in India. Therefore, I include the following indicators A dummy for district of the enterprise.…”
Section: Data and Summary Statisticsmentioning
confidence: 94%
“…International business is a long-term project that requires a large, integrated and developed network of infrastructures and services. Firms need significant resources to be able to access the knowledge of the foreign markets where they want to position themselves in an up-to-date manner [85]. Exports are the first step in this complex process.…”
Section: Do Cooperatives Perform Differently?mentioning
confidence: 99%
“…Speciālās ekonomikas zonas (Special economic zone) (turpmāk SEZ) ir stratēģiskas "no augšas uz apakšu" jeb valdības iniciatīvas, kurās uzņēmumiem tiek piedāvātas nodokļu un citas atlaides, īpaši atvieglojumi, infrastruktūra (Aggarwal, 2006), savukārt klasteri ir organiski veidojumi "no apakšas uz augšu", kuros iniciatīva nākt no klastera dalībniekiem (Zeng, 2011;Murphy et.al., 2009), taču veidojoties labvēlīgai videi, arī speciālajās ekonomiskajās zonās var veidoties klasteri (Zeng, 2011;Bhatt, Puri, Appolloni, 2012). Autore secina, ka gan SEZ, gan klasteris ir uzņēmumu ģeogrāfiska koncentrācija, taču SEZ gadījumā uzsvars tiek likts uz valsts atbalstu uzņēmumiem, kas darbojas ekonomiski atpalikušajos reģionos, turklāt SEZ nav svarīgi, kādas nozares uzņēmumi darbojas vienkopus.…”
Section: ģEogrāfiskais Tuvums (Viena Reģiona Ietvaros)unclassified